2021
DOI: 10.3389/fmars.2021.773870
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Stress Propagation in Benthic Invertebrates Caused by Acute pH Drop-Induced Metabolites

Abstract: Studies on pH stress in marine animals typically focus on direct or species-specific aspects. We here test the hypothesis that a drop to pH = 7.6 indirectly affects the intra- and interspecific interactions of benthic invertebrates by means of chemical communication. We recorded fitness-relevant behaviours of small hermit crabs Diogenes pugilator, green shore crabs Carcinus maenas, and harbour ragworms Hediste diversicolor in response to short-term pH drop, and to putative stress metabolites released by conspe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…We found these cues to elicit similar phenotypic responses as heat stress itself in naive receivers, which are the characteristics of a positive feedback loop (16). To date, only a few studies have shown that animals communicate to each other upon abiotic stress, such as heat and low pH (17,18). Zebrafish (Danio rerio) is a commonly used experimental model species, including for behavioural assays (19) and "omics" approaches (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found these cues to elicit similar phenotypic responses as heat stress itself in naive receivers, which are the characteristics of a positive feedback loop (16). To date, only a few studies have shown that animals communicate to each other upon abiotic stress, such as heat and low pH (17,18). Zebrafish (Danio rerio) is a commonly used experimental model species, including for behavioural assays (19) and "omics" approaches (20).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused mostly on cues released upon biotic factors such as injury (14) or disturbance (15). We have recently proposed that abiotic stress such as heat or low pH likewise elicits the release of olfactory cues, which we termed “stress metabolites” (16, 17). We found these cues to elicit similar phenotypic responses as heat stress itself in naive receivers, which are the characteristics of a positive feedback loop (16).…”
Section: Introductionmentioning
confidence: 99%
“…Variables such as microplastic levels, water level, temperature, and pH remained stable across our experiment, rather than fluctuating throughout the day. Daily and seasonal fluctuations in pH, for instance, can impact behavioural responses in marine organisms [ 64 , 65 , 66 ], including crustaceans [ 37 ] and involving stress-induced metabolites [ 67 ]. Such discrepancies may produce different effects in nature, so we recommend studies investigating whether our findings apply to wild hermit crab populations.…”
Section: Discussionmentioning
confidence: 99%
“…Frisch, 1938). We previously extended this mechanism to abiotic stress and identified specific classes of social metabolites (Feugere et al, 2021a; 2021b; 2023). Here, we confirm that heat stress responses can be indirectly transmitted between embryos via social metabolites activating immune-, cell structure- and keratin-related genes in receivers.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic ectotherms, such as zebrafish (Engeszer et al, 2007), may spawn in shallow waters where offspring experience high temperatures and environmental mutagens such as ultraviolet radiation (UVR) from sunlight (Dahms and Lee, 2010). Moreover, heat-stressed aquatic animals may release “social metabolites” that alter the phenotype of conspecifics not directly experiencing heat stress (Feugere et al, 2021a; 2021b). Embryos developing in clutches may have amplified stress responses to heat through chemical communication, the consequences of which have received little focus.…”
Section: Introductionmentioning
confidence: 99%